Los deportes no abordados y su influencia en la cultura deportiva - Astudillo Vásquez, Juan Carlos (2016)
Sports in Ecuador have always been the daily bread, especially football, in all its branches, however, that is what is happening with the other sports because sports journalism is so shallow with other Olympic branches and why the footballing expression is so wide. In the different chapters of this research project will be released sport in general practiced in Guayaquil and although not sport branches practiced daily, do not stop being Olympic, In sports history, there have been great exponents in various sports branches, as a result of their effort and motivation, have represented the country in Olympic fashion, making great awards, global, national and interprovincial, no clutch, sport more football popularity has been because it has best and greatest exponents globally…….